Triumphant Love The contextual, creative and strategic missionary work of Amy Beatrice Carmichael in south India - Kommers, J.(Hans) (AOSIS, 2017)
The book is a treasure trove for scholars in the field of science of religion who focus on comparative religion, spirituality and the reception of Christianity in India and Ireland. The strength of the book is its comprehensive scope, critical and narratological methodology, and the depth of the data analysis. The exposition of the contextual, creative and strategic missionary work of Amy Beatrice Carmichael in south India is innovative and highly informative. The book contains a high level of original research in that it goes beyond the existing research on the Carmichael biographies. The knowledge of the field is comprehensive and the number and quality of sources impressive. The biographic genre and methodology complement the extensive research in the book. This combination constitutes a genuine historical foundation for the scholarship. The main purpose of the book is to open the field of science to and pique the interest of professional theologians with an interest in missiology and in the valuable contribution of Amy Carmichael of Dohnavur. The book includes a comprehensive overview of the existing scholarly work on the topic and then makes a further innovative contribution to and, in the end, provides the most comprehensive picture of the work of Amy Carmichael to date. It will become the definitive reference book on the history of Christian missionary work in south India. It is original research and no part of the book was plagiarised from any other publication or has been published elsewhere before.